Towards a practice‐based view of strategy - Bromiley, Philip; Rau, Devaki (Strategic Management Journal, 2014)
Many studies in strategic management attempt to explain macro‐level firm behaviors or characteristics and/or the influence of such behaviors or characteristics on firm performance. Current strategy scholarship, however, rarely considers specific, actual techniques that managers might use to develop strategies or generally applicable firm practices. We propose a practice‐based view ( PBV ) of strategy scholarship to address this gap. In contrast with the resource‐based view emphasis on things that other firms cannot imitate, the PBV examines publicly known, imitable activities, or practices amenable to transfer across firms. We provide evidence for the PBV and discuss its contribution to strategy. The PBV has two important implications, one relating to potential explanations for performance and the other relating to the kinds of prescription strategy that scholars might offer . Copyright © 2014 John Wiley & Sons, Ltd.